2018
DOI: 10.1111/pan.13519
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective observational study of acquired subglottic stenosis using low‐pressure, high‐volume cuffed endotracheal tubes

Abstract: Summary Introduction The safety of cuffed endotracheal tubes in the neonatal and critically ill pediatric population continues to be questioned due to the theoretical risk of acquired subglottic stenosis. The incidence of acquired subglottic stenosis in the high‐risk mixed surgical and medical critically ill pediatric cohort using high‐volume, low‐pressure cuffed endotracheal tube policy has not yet been described. The aim of our study was to describe and evaluate the use and complication rate of cuffed ETT's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…The laryngeal injuries can be mucosal injuries like vocal cord erythema, edema, granulations or ulcerations to a more permanent sequelae like vocal cord palsy, arytenoids dislocation and subglottic stenosis. 6,11,[16][17][18][19][20][21][22][23][24][25][26][27][28] In addition, the tracheal injuries can be granulations in the initial stages to tracheal stenosis in the later stages. 29 In the present study, LTI observed were subglottic stenosis, granulation tissue in posterior commissure, vocal cord fixation and granulation tissue in the tracheal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laryngeal injuries can be mucosal injuries like vocal cord erythema, edema, granulations or ulcerations to a more permanent sequelae like vocal cord palsy, arytenoids dislocation and subglottic stenosis. 6,11,[16][17][18][19][20][21][22][23][24][25][26][27][28] In addition, the tracheal injuries can be granulations in the initial stages to tracheal stenosis in the later stages. 29 In the present study, LTI observed were subglottic stenosis, granulation tissue in posterior commissure, vocal cord fixation and granulation tissue in the tracheal wall.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] With the advent of high-volume low pressure cuffed tubes, patient can be ventilated through the endotracheal tube for up to 3 weeks. 3,11 The presence of endotracheal tube in direct contact with larynx and trachea can provoke injuries to its mucosa and submucosal layer which in turn can lead to ulcerations, granulation tissue and stenosis. 12 These injuries may be temporary in the beginning which can become a permanent sequelae later.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for developing subglottic stenosis are: multiple intubation; incorrectly sized tracheal tube; low birth weight; underlying clinical condition and duration of mechanical ventilation, rather than the type of tube used . A recent retrospective study of 5309 children admitted to critical care, of whom 3361 were ventilated with a high‐pressure low‐volume cuffed tube, reported only eight patients with acquired subglottic stenosis . Five of these patients required major airway correction surgery and all had been born prematurely, initially intubated with uncuffed tubes in an external neonatal intensive care unit.…”
Section: Subglottic Stenosismentioning
confidence: 99%
“…GERD has been associated with SGS in both adults and children [19,20]. In children, SGS is most commonly associated with pre-term infants and/or low birth rate [21,22].…”
Section: Introductionmentioning
confidence: 99%